Aplikasi Deteksi Gempa Secara Realtime Berbasis Mobile di Indonesia - Gilang Zakaria Putra; Nanda Bima Mahendra; Muhammad Bima Indra Kusuma; Galih Anggi Satriawan (LPPM STIKI MALANG, 2019)
The purpose of this research is the development of applications that can detect earthquakes in realtime. This mobile-based realtime earthquake detection application can provide notifications to all smartphones that have the application installed. In addition, notifications sent will also trigger an alarm on the smartphone. This earthquake detection application gets data from the Rest API that has been provided by BMKG. This detection application also utilizes Google products, namely Firebase Cloud Messaging (FCM), where Firebase Cloud Messaging has a feature of helping a webservice or application to send notifications in realtime. In addition, this application also utilizes GPS (Global Positioning System) which will be used to calculate the distance of the user's location from the earthquake's epicenter.